Similar Wear in Total Hip Arthroplasties with Metallic or Zirconia Femoral Heads - Cohn, Randy M. (Springer-Verlag, 2008)
Ceramic femoral heads have been used in an attempt at reducing polyethylene wear of total hip arthroplasties. Clinical results with zirconia femoral heads have been mixed. This study was undertaken to compare the polyethylene wear and incidence of periprosthetic osteolysis in total hip replacements performed using a 28-mm zirconia versus a 28-mm cobalt chromium femoral head. Thirty-five hips with a 28-mm cobalt chromium head and 68 hips with a 28-mm zirconia head were evaluated after a minimum follow-up of 2 years (average, 4.0 years; range, 2.0 to 9.1 years). A monoblock acetabular component was used in all patients. Polyethylene wear was measured in serial radiographs from 58 of the hips utilizing a computer-assisted vector wear technique. Periacetabular osteolysis developed in three patients (two with a zirconia head and one with a cobalt chromium head). The total wear and the annual wear rate were 0.48 mm and 0.11 mm/year for the cobalt chromium heads and 0.53 mm and 0.14 mm/year for the zirconia heads, respectively. We found no benefit with respect to the rate of polyethylene wear or incidence of osteolysis with the use of zirconia femoral heads.